Serati Banten Empowerment Through Serati Banten Regeneration Training and Digital Marketing Socialization to Increase the Productivity of UMKM Serati Banten in the Village of Batuan, Gianyar - Putu Eka Trisna Dewi; I Nyoman Suargita; Ni Kadek Astariani; Putu Gede Denny Herlambang; Tjokorda Gde Agung Wijaya K.S (Fakultas Hukum, Universitas Warmadewa, 2023)
Bali is an area with cultural traditions that are still well preserved. Batuan is one of the many villages in Gianyar which still preserves its conserve and culture from the past to the present. In Bali, it is known for the many and dense religious ceremonies and traditional ceremonies where each procession uses an ceremony called banten. Serati Banten is the spearhead of all ceremonial activities that are held. Serati Banten is someone who has expertise, both in terms of ethics and ability, in making religious ceremonial equipment, especially banten and offerings in the Hindu community. Banten made must be based on sincerity and good ethics so as to enhance the meaning and meaning of a ceremony. Seeing the importance of the role of offerings in traditional and religious activities in Bali, Ngurah Rai University through the community service program KAT Group 1 held training on regeneration of offerings and socialization and digital marketing training to increase the productivity of UMKM in Batuan, Gianyar Village. Ngurah Rai University through KAT UNR Group 1 also handed over aid for the production of Banten production which was handed over by the head of the accompanying lecturer along with other accompanying lecturers to the chairperson of the Banten Banten Association and its members.